Isolation,Characterization and Optimization of Wild Type Sinorhizobium meliloti to Produce High Concentrations of Indole Acetic Acid - Kanaan, Ibtihal Idrees; Al-Barhawee, Najwa Ibrahim Khaleel (Iraqi Journal of Science, 2021)
Rhizobium bacteria was isolated from the root nodules of Medicago sativa plants and, based on morphological and some biochemical properties, it was characterized as Sinorhizobium meliloti. We studied the ability of this isolate, as well as that of Agrobacterium rhizogenes R1601, to produce the auxin indole acetic acid (IAA). For purposes of control, both isolates, in the absence of tryptophan-L, were similarly tested. The identification of IAA was achieved by checking the colour reactions with Salkowski’s reagent. Low amounts (23, 69 and 26,77 µɡ/ml) of IAA were produced by S.meliloti and A.rhizogenes after 24 and 72 hours of incubation, respectively. S.meliloti was distinguished by the high production of this auxin (612µg/ml) when adding 0.1% tryptophan to the growth medium (YEM), as compared to the amount of its production by the other bacteria. Therefore, this isolation was used to determine the highest production of IAA at optimal conditions, which reached to 553,550 and 610,662 µg/ml in liquid YEM medium supported with tryptophan-L (both at 0.5 and 1.0%) and a medium supported with glucose and lactose sugar (10%), after 72 hours of incubation, respectively. The 72-hour incubation period was better than that of 24-hour in obtaining an additional amount of IAA, which ranged between 0.6 and 0.7g/l. A spot of IAA produced by rhizobium bacteria was created corresponding to the standard spot of IAA in the thin layer chromatography (TLC) detection experiment.